The Effect Of Entrepreneurship, Remittances And Urbanization On Income Inequality In Developing Countries: Leveraging On Rural Development And Infrastructure - Mohamad, Nurul Muna (2022)
Income inequality problem is a vital agenda to deal with, especially for developing countries. In the presence of high income inequality in many developing countries, solutions are certainly welcome. Several factors are deemed important to address the problem of income inequality in this study, which include entrepreneurship, remittances and urbanization.